Female Cross-Dressing in Chinese Literature Classics and their English Versions - Wing Bo Tso, Anna (International Studies. Interdisciplinary Political and Cultural Journal, 2014)
Cross-dressing, as a cultural practice, suggests gender ambiguity and allows freedom of self expression. Yet, it may also serve to reaffirm ideological stereotypes and the binary distinctions between male and female, masculine and feminine, homosexual and heterosexual. To explore the nature and function of cross-dressing in Chinese and Western cultures, this paper analyzes the portrayals of cross-dressing heroines in two Chinese stories:《木蘭辭》 The Ballad of Mulan (500–600 A.D.), and 《梁山伯與祝英台》The Butterfly Lovers (850–880 A.D.). Distorted representations in the English translated texts are also explored.